2005
DOI: 10.1210/me.2004-0064
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that an Isoform of Calpain-10 Is a Regulator of Exocytosis in Pancreatic β-Cells

Abstract: Calpain-10 (CAPN10) is the first type 2 diabetes susceptibility gene to be identified through a genome scan, with polymorphisms being associated with altered CAPN10 expression. Functional data have been hitherto elusive, but we report here a corresponding increase between CAPN10 expression level and regulated insulin secretion. Pancreatic beta-cell secretory granule exocytosis is mediated by the soluble N-ethylmaleimide-sensitive fusion protein attachment receptor protein complex of synaptosomal-associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 53 publications
12
93
0
1
Order By: Relevance
“…3B). Importantly, we have previously shown that exocytosis in pancreatic β-cells is accompanied by partial proteolysis of SNAP-25 [9]. Interestingly, while we again observed SNAP-25 cleavage in immunoblots of INS-1 cells incubated with secretagogue cocktail (Fig.…”
Section: Snapin Binding With Snap-25 Precedes Granule Exocytosissupporting
confidence: 69%
See 1 more Smart Citation
“…3B). Importantly, we have previously shown that exocytosis in pancreatic β-cells is accompanied by partial proteolysis of SNAP-25 [9]. Interestingly, while we again observed SNAP-25 cleavage in immunoblots of INS-1 cells incubated with secretagogue cocktail (Fig.…”
Section: Snapin Binding With Snap-25 Precedes Granule Exocytosissupporting
confidence: 69%
“…3B). The absence of an interaction between snapin and the partially proteolysed SNAP-25 protein therefore indicates that snapin binds to SNAP-25 via its N-terminal Sn1 domain, as it is within this region of SNAP-25 that we have previously found SNAP-25 to be proteolytically cleaved by calpain-10 during exocytosis [9]. As such the larger clipped fragment of SNAP-25, lacking its Nterminus, is no longer observed on Western blots of samples immunoprecipitated with snapin following secretagogue-stimulated partial proteolysis.…”
Section: Snapin Binding With Snap-25 Precedes Granule Exocytosismentioning
confidence: 82%
“…Calpain-10 was identified in human pancreatic islets and there is a positive correlation between calpain-10 levels and insulin release in response to a secretagogue cocktail in INS-1 cells. Calpain-10 is involved in the first phase of exocytosis and it binds to the plasma membrane SNARE complex and affects SNAP-25 proteolysis [52]. Calpain-10 has been suggested to stimulate apoptosis in response to fatty acids.…”
Section: Calpains and Niddmmentioning
confidence: 99%
“…When Ca 2+ was removed from the supernatant, these reactions were not induced. These results indicate that the intracellular Ca 2+ concentration increased by glucose stimulation can activate calpain-10 and break SNAP25 (a SNARE protein), thereby inducing fusion of insulin granules to the membrane of the β cells [32]. However, considering the absence of key 54-kD proteins among the reported calpain-10 isoforms, further analysis is required.…”
Section: ) Calpain and Insulin Secretionmentioning
confidence: 96%